The Influence of Social Function of Mobile Game Augmented Reality and Virtual Reality Environment on Mobile Phone Users’ Addiction - Liang, Chuan; Song, Yang; Wang, Bin (Wireless communications and mobile computing, 2022)
The study explores the influence of social function in mobile game augmented reality (AR) and virtual reality (VR) environments on mobile phone users’ addiction. This study uses the mixed research method of social function on the basis of enhancement and VR and mathematical statistics analysis to study the situation of mobile game addiction. In this research work, a collision detection algorithm (CDA) with machine learning is proposed. The collision detection algorithm aids in the detection of the intersection of two objects in the virtual environment and is implemented in games that support augmented reality and virtual reality technologies. It is assumed that the intuition for playing games is obtained from social networking sites, which may lead to the person becoming addicted to playing. This research focused on the analysis of AR and VR-related games by considering mean, standard deviation, and error parameters.